Microstructure evolution and superelasticity of layer-like NiTiNb porous metal prepared by eutectic reaction. (15th January 2018) - Wang, Liqiang; Xie, Lechun; Zhang, Lai-Chang; Chen, Liangyu; Ding, Zihao; Lv, Yuting; Zhang, Wei; Lu, Weijie; Zhang, Di
Abstract: This work combines several techniques into a novel method to manufacture NiTiNb layer-like porous structures with 3D interconnected channels, which are of vital importance in the biomedical field. NiTi wires and Nb foils are used herein to prepare NiTiNb layer-like porous materials via in situ eutectic reaction. Microstructure, phase transformation and superelasticity of the resultant NiTiNb layer-like porous material are analyzed and discussed, and the interface between NiTi wires and the solidified NiTiNb eutectic region are also studied. Dislocations and stacking faults occurring at interfaces accelerate the eutectic phase transformation. Meanwhile, rod-like eutectic phase pins the motion of screw dislocations, which is beneficial for stress-induced R martensite nucleation. It is believed that much more superelastic recovery and elastic recovery for such a layer-like porous structure are attributed to formation of more martensites during deformation. Furthermore, both reorientation and subsequent de-twinning of <011> type II twins result in the observed stress-plateau, thereby promoting the superelastic recovery. Graphical abstract: Image